Frações contínuas e equações diofantinas lineares e não-lineares - Pereira Júnior, Jackson (2015)
In this work a different proposal is presented for the study of continued fractions, where properties will be addressed on representations of rational and irrational numbers on the form of continued fraction. In addition, the study of properties related to continued fractions, we will also address the study of its convergent, highlighting the most important property, and applying the use of continued fractions in solving linear Diophantine equations and also in the resolution of so-called Pell equations.